THE CONCEPT OF SOCIAL RISK: A GEOGRAPHICAL APPROACH - Lupu, Laura (Quaestiones Geographicae, 2019)
Social risk is an interdisciplinary concept used with various meanings in the social and in the natural sciences. The article presents some of the social insights into this concept, particularly in connection with the global environmental research project and with geography. The special dimension of social risks, as well as some current methodological aspects regarding models and the main indicators used in the multidimensional assessment of social risks are analysed at local, regional and national levels. Of special interest is the link between social risks and a series of key-concepts, such as: hazard, impact, social vulnerability, resilience, adaptive capacity.